If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x-2+x=2(x-7)
We move all terms to the left:
-3x-2+x-(2(x-7))=0
We add all the numbers together, and all the variables
-2x-(2(x-7))-2=0
We calculate terms in parentheses: -(2(x-7)), so:We get rid of parentheses
2(x-7)
We multiply parentheses
2x-14
Back to the equation:
-(2x-14)
-2x-2x+14-2=0
We add all the numbers together, and all the variables
-4x+12=0
We move all terms containing x to the left, all other terms to the right
-4x=-12
x=-12/-4
x=+3
| 4.4(x-2.75)=-13 | | 3c+36=90 | | 3c+36=90 | | 6/7x+5=-1/7x-4 | | -17=7y+2(y+4) | | 2x=126° | | 69(2)-x=55 | | 1/4z+3/4z=2 | | 4=11-3x/4 | | 3x+5-2x-5-x=0 | | 0.4x+0.9=0.2x+0.6 | | 8x-15Y=35 | | 1/3y=1/6y | | -t/6.2+7=9 | | 5n=10n+5 | | −21= −21−b−21−b | | b+2.48-4=4.04 | | |7(x+3)|+5=33 | | b+2.48–4=4.04 | | f4−1.4=2.82 | | 3(x+2)=21-6x | | 5(7a-7)=105 | | P=1.5x+12 | | 2e–3–1/5e=7/5+3e+4 | | 4+3(x+2)=110 | | 3(x+2)+9=3x+3 | | 0.2x+3.1=0.7x-0.4 | | -25=-2x+7;16 | | |-4c+15|=35 | | |8x-1|=4 | | 5x+40+2x-60=180° | | 3x-5=6x+35 |